PENINGKATAN MINAT BELAJAR MEMBACA KELOMPOK B TK MUSLIMAT NU AL-HIDAYAH KUDIKAN LAMONGAN - Anita Munawwaroh; Erfitra Rezqi Prasmala; Titik wijayanti; Latifatul Izza (JPM PAMBUDI, 2022)
Interest in learning to read in class B at Muslimat NU Al-Hidayah Kindergarten because the teacher is not optimal in applying the learning method to read according to the rules, besides that the child's desire to read in activities in kindergarten often experiences this difficulty due to the ability and ability of children to understand one another. others are different, this is because children are not yet able to master vocabulary and letters of the alphabet. This service activity was carried out at the Muslimat NU Al-Hidayah Kudikan Lamongan Kindergarten. The work program that has been prepared in these activities is more focused on mentoring programs (in the form of group B reading learning assistance). Implementation of Activities Children who learn to gain new knowledge, and can apply what is explained or taught by students who carry out community service activities at the PAUD Al-Hidayah Kudikan Lamongan building. As for the results they got, namely teachers could practice reading learning methods and media that were interesting and could be practiced at school or at home, so as to increase interest in reading Muslimat NU Al-Hidayah Kudikan Lamongan Kindergarten students.